Buying and Selling of Ulayat Land Jointly Owned by Several Tribes in Jayapura City - Bastanta Kurnia Ginting; Musakkir Musakkir; Sri Susyanti Nur (Journal of Social Science, 2022)
his study is based on the fact that not all Ondoafi (clan’s leader) understand their position and authority in buying and selling ulayat land, especially for ulayat land whose ownership is carried out jointly by several tribes. This study aims to discuss the legal position of buying and selling customary land in Jayapura City, the Port Numbay Customary Council (LMA) in resolving disputes over customary land in Jayapura City, and position and role of tribal chiefs in Skouw Mabo village. Jayapura City is in the process of buying and selling customary land. This study uses empirical legal research using a structural approach, a stratification approach, and a pluralism approach. The data used is in primary legal materials, then analyzed using qualitative methods. The results obtained are that first, the law of buying and selling customary land carried out in Jayapura City is valid as long as it has received approval from Ondoafi as a leader in a government system that uses customary law. Second, the role of the Port Numbay Traditional Deliberation Institution (LMA) organizationally is as a forum when there is a dispute over communal land in Jayapura City. Moreover, third, the role of the tribal chief (keret) in carrying out the process of buying and selling ulayat land in Skouw Mabo Village on his land, the tribal chief does not have full rights or cannot personally sell his ulayat land.